Integration of Azerbaijan into North Atlantic Alliance Treaty and European Union - Sharifov, Jamal (2008)
In this thesis, student will research and analyze importance of Azerbaijan’s integration and cooperation with the NATO and the EU. Author will detect political expectations of Azerbaijan from the cooperation and integration into NATO and EU. Student will evaluate the quality of these expectations; however he will examine and evaluate the quality of mutual relations as well. The work will apply the method of comparative analysis of relations of Azerbaijan with NATO and EU in order to examine with which of these structures Azerbaijan has closer relations. Author will include also analysis of external negative factors are influence to the integration of Azerbaijan into NATO and EU (mainly the position of Russia and Iran opposing this political course). The work will address following questions as well: to what extent is Azerbaijan ready for integration; how NATO and EU are willing to foster cooperation with Azerbaijan; how strong is official course of Azerbaijan towards NATO and EU. Main .